Dinâmica da caducifolia e composição da serrapilheira de poincianella pyramidalis (Tul.) L. P. Queiroz em áreas de caatinga sob pastejo caprino - Macêdo, Italvan Milfont (2018)
The litter comprises the most important means of transfer of essential elements of the vegetation to the soil, and important fodder resource to feed small ruminants during the dry period. The objective of this study was to evaluate the importance of the leaf litter of Poincianella pyramidalis (Tul.) for the maintenance of soil fertility and feeding of small ruminants in the climatic conditions of the semiarid region of Paraíba. The experiment was conducted at the Experimental Station of São João do Cariri, PB in an area of 9.6 ha, subdivided into three pickets, managed during the whole experimental period with different stocking rates 0.14 UA ha-1 year (area I), 0.07 UA ha 1 year (area II) and no animal (AIII) goats. The collections were carried out between March/2016 and September/2017, totaling 18 months, during which the contribution of litter was quantified. During one year the leaflet decomposition was evaluated through the mass loss using litter bags, and the chemical composition of the leaflets. Spatial temporal geostatistics was used for foliar input, considering points and months of sampling, to adjust semivariogram models and later interpolation by kriging. For the composition data, the experimental design was completely randomized, with the data submitted to analysis of variance and the means compared by the Tukey test at 5% of significance. The average production of 1,312.5 was quantified; 1,550.4 and 1,374.5 kg MS ha-1 and 85.1; 103.5 and 95.5 kg DM ha-1 , in areas I, II and III, respectively for March to April 2016 and January to September 2017. The leaflets presented 35% decomposition for a period of one year. The CP content of leaves (leaflets + petioles) ranged from 71.5 to 91.1 g/kg DM between the evaluated areas. The leaflet fraction presented 337.3, 212.5 and 98.4 g/kg DM, respectively, for NDF, FDA and LDA. On an annual basis, the order of nutrient deposition was: Ca>N>K>Mg>P>Fe>Mn>Zn. It was concluded that during the dry period there is little change in the composition of the material and the areas managed with greater intensity of goat grazing tend to reduce the C:N ratio.